2015
DOI: 10.5603/nmr.2015.0018
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion lung scintigraphy for the prediction of postoperative residual pulmonary function in patients with lung cancer

Abstract: This study shows that planar LPS may be applied for prediction of postoperative pulmonary function in patients qualified for pneumonectomy and lobectomy. If actual FEV1postop value is to be ≥ 800 mL, predicted value should exceed 1000 mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Many studies have tried to predict the postoperative pulmonary function on the basis of reduced perfusion of the involved lung which is marked for resection. [ 6 14 15 ] Bolliger et al showed that perfusion and quantitative CT-based predictions of postoperative pulmonary function are useful irrespective of the extent of resection, but perfusion-based results were the most accurate. They also concluded that anatomical segment counting calculations for resection should be reserved for resection not exceeding lobectomy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have tried to predict the postoperative pulmonary function on the basis of reduced perfusion of the involved lung which is marked for resection. [ 6 14 15 ] Bolliger et al showed that perfusion and quantitative CT-based predictions of postoperative pulmonary function are useful irrespective of the extent of resection, but perfusion-based results were the most accurate. They also concluded that anatomical segment counting calculations for resection should be reserved for resection not exceeding lobectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in literature have shown a good correlation of the actual postoperative FEV1 with prediction made from perfusion only studies. [ 6 12 18 ] Researchers also evaluated the role of SPECT and SPECT/CT methods in predicting the postoperative lung function. Kovacević-Kuśmierek et al showed that performing planar perfusion scintigraphy is not inferior to tridimensional methods such as SPECT and SPECT/CT in the quantification of split lung function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulmonary function test (PFT) using spirometry is the current standard method of evaluating pulmonary function. While many studies have evaluated the change in lung volume before and after lung resection and correlated this with pulmonary function test results [ 1 3 ], there is very little evidence on the changes in ventilation perfusion ratio (V/Q) before and after lung resection. This is considered to be at least in part due to the practical difficulty of frequently performing ventilation perfusion scans using radioneuclides, as well as its low spatial resolution.…”
Section: Introductionmentioning
confidence: 99%